A compact CCD‐monitored atomic force microscope with optical vision and improved performances. Issue 9 (26th June 2013) - Mingyue, Liu; Haijun, Zhang; Dongxian, Zhang
ABSTRACT A novel CCD‐monitored atomic force microscope (AFM) with optical vision and improved performances has been developed. Compact optical paths are specifically devised for both tip‐sample microscopic monitoring and cantilever's deflection detecting with minimized volume and optimal light‐amplifying ratio. The ingeniously designed AFM probe with such optical paths enables quick and safe tip‐sample approaching, convenient and effective tip‐sample positioning, and high quality image scanning. An image stitching method is also developed to build a wider‐range AFM image under monitoring. Experiments show that this AFM system can offer real‐time optical vision for tip‐sample monitoring with wide visual field and/or high lateral optical resolution by simply switching the objective; meanwhile, it has the elegant performances of nanometer resolution, high stability, and high scan speed. Furthermore, it is capable of conducting wider‐range image measurement while keeping nanometer resolution. Microsc. Res. Tech. 76:931–935, 2013. © 2013 Wiley Periodicals, Inc.